Development of loop-mediated isothermal amplification (LAMP) SYBR Green I assay as screening test for detection of 4 strains of Salmonella spp. in feed and feed ingredients - Masphol, Sithisak; Paraksa, Nuanchan; Nuchchanart, Wirawan (Agriculture and Natural Resources, 2022)
Salmonella spp. are a group of gram negative and pathogenic bacteria that cause food poisoning in humans and animals. Traditionally, the Salmonella causative source has been attributed to animal products, feed and feed ingredients. Conventional detection methods of Salmonella spp. are time-consuming since they take 5 d. Herein, a LAMP-SYBR green I test integrated with LAMP (loop-mediated isothermal amplification) was developed to increase the yield of the Salmonella invasion gene (InvA) with the SalinvA01 primer set and identification of Salmonella spp. by pre-enrichment for 4 hr and a reaction time within 60 min at an optimized temperature of 62°C. Subject to these optimized conditions, the detection limits of the designed LAMP for Salmonella spp. pure culture were 1.33×103 colony forming units (cfu)/mL or 26.6 cfu/tube. LAMP-SYBR green I and LAMP-AGE showed no cross-reactivity with 15 isolates of non-Salmonella spp. including Escherichi coli, Listeria monocytogenes, Staphylococcus aureus, Bacillus cereus, Micrococcus luteus, Microbacterium spp., Corynybacter glutamicum, Pichia membranaefaciens, Rhodotorula mucilaginosa, Serratia marcescens and Proteus mirabilis. Among the 24 samples of feed and feed ingredients that were used to evaluate artificial contamination and enrichment of Salmonella spp., LAMP-SYBR green I and LAMP-AGE demonstrated 100% accuracy compared to PCR and conventional methods. In conclusion, the LAMP-SYBR green I assay was confirmed to be highly specific, accurate, fast and convenient, and to have low detection limits. The results can be provided in 1 hr using isothermal conditions, so there is no need to use a thermocycler. Hence, the developed assay can be utilized for screening Salmonella spp. contamination in feed and feed ingredients.